Mitigating the associated risks in the unregulated use of crypto-currencies in South Africa through an effective legal framework - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2017.